Role of Exercise Tolerance Test in the Screening of Suspected Myocardial Ischemia in Bangladeshi Patients (Bangladesh Heart Journal, 2019)
Background: Ischemic Heart Disease (IHD) is preventable and reversible if early screening and elimination of the risk factors like life style modification and dietary intervention can be done. Exercise Tolerant Test (ETT) has become an important diagnostic tool to evaluate patient with suspected or known case of ischemic heart disease.Objective: To determine the frequency of IHD among subjects who presented with chest pain and to identify the common indications for ETT.Methodology: It was a cross-sectional study; the data was collected from ETT Unit of Mugda Medical College Hospital, Dhaka, Bangladesh using standard Bruce protocol.Result: Out of 200 patients, there were 124(61%) male and 78(39%) female who presented in the cardiology department for ETT. Common indications for ETT were evaluation of chest pain 180(90%), followed by general check-up 14(7%), post-PCI evaluations 4(2%) and post- CABG evaluation 2(1%).Presenting complaints were typical angina 12(6%), shortness of breath 56(28%), nonspecific chest pain 82(41%), chest compression 46(23%) and others 4(2%). Exercise ECG showed no ST changes in 138(69%) patients. The most common risk factors were hypertension, diabetes, smoking and obesity. Majority of the subjects 136(68%) were test negative whereas 42 (21%) were test positive and 22(11%) were test equivocal.Conclusions: It is concluded that most of the subjects presenting with the suspected symptoms of myocardial ischemia were negative for IHD, and so why we advocate the use of ETT as a screening tool in patients who presents with features simulating angina. This will prevent unnecessary hospital admission.Bangladesh Heart Journal 2019; 34(2) : 122-126